PROBLEMS OF FUNDAMENTAL, SOCIO-CULTURAL METHODS AND CLASSICAL APROACH IN TECHING ENGLISH - Kushakov, Yusup (Журнал иностранных языков и лингвистики, 2023)
The article raises problems about basic methods and approaches in teaching English as integral parts in teaching English and foreign languages as a whole. According to the author, students of different ages and most often involve learning the language from scratch. As the author points out, tasks of the teacher include traditional, but important aspects of pronunciation, the formation of a grammatical base, the elimination of the psychological and language barriers that impede communication.